Peran Notaris Dalam Pembuatan Akta Waris Bagi Masyarakat Adat Bali - Permata Sari, Dewa Ayu Indah (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2025)
The decision of the Pakraman Village Main Council provides an opportunity for women to obtain inheritance rights, but not a few cause disputes, so the role of notaries in making inheritance deeds is needed to provide legal certainty. This research is a normative juridical research, with primary and secondary legal materials collected through the process of identification and inventory of relevant laws and regulations. The results show that there is still dualism in the making of deeds / certificates of inheritance in Indonesia, class distinctions cannot be eliminated. The role of a notary in creating an authentic deed of inheritance based on Balinese customary law is only as a mediator who assists the heirs who have agreed to make a deed of inheritance. The notary has the role of providing advice, legal opinions, and solutions to the heirs and following the agreement of the heirs according to Balinese customary law.